2016
DOI: 10.1186/s41043-016-0049-x
|View full text |Cite
|
Sign up to set email alerts
|

Consanguinity and its socio-biological parameters in Rahim Yar Khan District, Southern Punjab, Pakistan

Abstract: BackgroundRahim Yar Khan (RYK) District is a multi-ethnic assemblage of both ancient and migrated communities in Southern Punjab, Pakistan. There is a paucity of knowledge on the bio-demographic structure of this endogamous population.MethodsWe have carried out a cross-sectional epidemiological study in RYK District and recruited 2174 random Muslim married females. Detailed account of marital union types, level of consanguinity, and subject’s fertility, was taken.ResultsThe analyses of these data revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 20 publications
3
32
2
1
Order By: Relevance
“…58.5%. 21 Similar findings have also been reported by two independent groups of researchers in 2013 from Iraq 22 and Iran. 23 Contrary to this finding an association of parents' consanguinity and emergence of DS was observed in a North American study.…”
Section: Discussionsupporting
confidence: 81%
“…58.5%. 21 Similar findings have also been reported by two independent groups of researchers in 2013 from Iraq 22 and Iran. 23 Contrary to this finding an association of parents' consanguinity and emergence of DS was observed in a North American study.…”
Section: Discussionsupporting
confidence: 81%
“…Among the subjects with neuromuscular anomalies, the rate of consanguinity was 30%. This is rather surprising as several studies have advocated a high incidence of consanguineous marriages, that is, 57-62%, in various Pakistani populations [34][35][36]. Nonetheless, the increased incidence of CA is generally attributed to a high rate of parental consanguinity in Pakistani society [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study did not found any significant differential in the consanguineous union and no-consanguineous samples with respect to pre or post-natal mortalities and child morbidities. 15 In contrast, in Qatar, a study of 1,515 women found 54% consanguineous marriages and the most common form of that was the marriage between first cousins. Inborn, children of these couples had a significantly higher rate of asthma, intellectual disability, epilepsy, and diabetes compared with children of non-consanguineous couples.…”
Section: Introductionmentioning
confidence: 95%